Assessing reading difficulties: the validity and utility of current measures of reading skill. - Nation, K; Snowling, M (1997)
BACKGROUND: Accurate assessment of reading difficulties is clearly important if appropriate support and remediation is to be provided. Many different reading tests are routinely used yet it is not clear to what extent different tests tap the same underlying skills. AIMS: The nature of the relationships between different tests of reading accuracy, reading comprehension and linguistic comprehension is investigated in this paper. SAMPLES, METHODS AND RESULTS: In study 1, 184 7-10 year old children completed a listening comprehension test, three tests of reading accuracy (reading of nonwords, single words and text) and two tests of reading comprehension (test comprehension and sentence completion). While sentence completion was well accounted for by individual differences in word recognition, text comprehension was more heavily dependent on listening comprehension. Study 2 compared the performance of children with poor comprehension skills with controls matched for age, nonverbal ability and decoding skill. The poor comprehenders had greatest difficulty with those tests most heavily dependent on linguistic comprehension and least difficulty on purer measures of decoding. CONCLUSIONS: These findings show that different reading tests measure different aspects of the reading process and that caution should be exercised when selecting tests for the assessment of reading difficulties.